Hermann Franz Matthias Mutzenbecher. Ein Hamburger Versicherungsunternehmer - Schröder, Hans Joachim (Mäzene für Wissenschaft, 2008)
The long-established family of the Mutzenbechers has repeatedly played an important role in the life of the Hanseatic city. One of the outstanding representatives of the family is Hermann Franz Matthias Mutzenbecher, donor of the Hamburg Scientific Foundation. Together with his younger brother Franz Ferdinand he headed the Mutzenbecher Group between 1901 and 1931, a group of companies which included Albingia Versicherungsgesellschaft. The insurance transactions that determined the life of H. F. M. Mutzenbecher are in their ups and downs a reflection of global history.